Evaluation of the presence of emerging contaminants in wastewater and seawater using automated solid-phase extraction and ultra-high-performance liquid chromatography coupled to tandem mass spectrometry - Julia Méndez-Catalán; Cristina Socas-Hernández; Gabriel Jiménez-Skrzypek; Javier Hernández-Borges; Javier González-Sálamo (Journal of Chromatography Open)
The presence of emerging contaminants in water constitutes one of the main ways of human exposure to them, which can cause severe effects on health. In this sense, their adequate elimination through appropriate treatments plays a fundamental role, being necessary to monitor the effluents from wastewater treatment plants, as well as the areas close to their discharge. The aim of the present work has been the development and validation of an analytical methodology to determine 15 organic contaminants of emerging concern in wastewater as well as in seawater samples using an automated solid-phase extraction system and an ultra-high-performance liquid chromatography coupled to tandem mass spectrometry instrument. Matrix-matched calibration showed good linearity with determination coefficients ≥ 0.990. Likewise, matrix effect assessment showed a significant signal suppression in almost all the analytes demonstrating the need to consider such effect for a proper quantification of the analytes. Recovery values ranged from 74.7 to 109% with relative standard deviation values ≤ 20.5% for most analytes. Regarding seawater and wastewater samples, 11 of the target analytes were detected in, at least, one sample at concentrations from below limit of quantification of the method to 217 ± 92 ng l-1 in seawater and up to 2340 ± 107 ng l-1 in wastewater samples.